Managing Arrow-Trerotola Percutaneous Thrombolytic Device Complications - Simpson, Russell O.; Gaba, Ron C.; Lipnik, Andrew J. (Seminars in Interventional Radiology, 2019)
Dialysis access interventions are frequently performed by interventional radiologists. Several commercially available percutaneous thrombolytic devices can help restore patency to thrombosed arteriovenous access circuits. The Arrow-Trerotola Percutaneous Thrombolytic Device is one such device, and has a long track record of safe and effective use. However, like any medical device, complications can occur during its use. This article describes three complications and associated management strategies utilizing fundamental interventional radiology techniques of balloon tamponade, stent placement, and snare mediated foreign body retrieval.
Keywords: dialysis interventions; venous rupture; foreign body retrieval; interventional radiology